Bovine Parainfluenza-3 Virus Detection Methods and Prevalence in Cattle: A Systematic Review and Meta-Analysis - Gebremeskel Mamu Werid; Thien D. Van; Darren Miller; Farhid Hemmatzadeh; Robert W. Fulton; Roy Kirkwood; Kiro Petrovski (Animals, 2024)
Bovine parainfluenza-3 virus (BPI3V) is an important respiratory pathogen in cattle, contributing to syndromes in the bovine respiratory disease complex (BRDC). Despite its significance, the understanding of its prevalence remains fragmented, especially within the larger framework of BRDC. This systematic review and meta-analysis aimed to determine the global prevalence of BPI3V in cattle using varied detection methods and to highlight associated risk factors. Of 2187 initially retrieved articles, 71 were selected for analysis, covering 32 countries. Depending on the detection method employed, the meta-analysis revealed significant variations in BPI3V prevalence. In the general cattle population, the highest prevalence was observed using the antibody detection method, with a proportion of 0.64. In contrast, in cattle with BRDC, a prevalence of 0.75 was observed. For the antigen detection method, a prevalence of 0.15 was observed, exclusively in cattle with BRDC. In nucleic acid detection, a prevalence of 0.05 or 0.10 was observed in the general and BRDC cattle populations, respectively. In virus isolation methods, a prevalence of 0.05 or 0.04 was observed in the general and BRDC cattle populations, respectively. These findings highlight the differences in the detection ability of different methods in identifying BPI3V. Other factors, such as country, study year, coinfections, farm size, the presence of respiratory signs, sex, and body weight, may also affect the prevalence. Most studies were anchored within broader BRDC investigations or aimed at detecting other diseases, indicating a potential under-representation of focused BPI3V research. BPI3V plays an important role in BRDC, with its prevalence varying significantly based on the detection methodology. To further understand its unique role within BRDC and pave the way for targeted interventions, there is an evident need for independent, dedicated research on BPI3V.